IMPLEMENTASI KEBIJAKAN SI N’DUK (SISTEM INFORMASI ONLINE DOKUMEN KEPENDUDUKAN) DALAM MENINGKATKAN EFEKTIVITAS PELAYANAN PUBLIK DI KABUPATEN BOJONEGORO - Zahra Ayu Hanida (Sekolah Tinggi Pariwisata Mataram, 2023)
The Si N'duk application was launched to reduce the intensity of face-to-face meetings between applicants and population administration service officers iin ithe imidst iof ithe iCovid - 19 ipandemic. The Si N'duk application can be downloaded on the Android Smartphone Playstore. The Head of Information Management and Data Utilization of the Bojonegoro Dispendukcapil, revealed that the application was not maximized because it could only be used for KTP and KK arrangements. This application basically simplifies the adminduk service process, namely applicants download their respective smartphone ID applications, then iregister iby ientering itheir iNIK number iand iKK number. iThe applicant uploads the resident requirements file for managing population documents in the application which will then be processed by the population administration officer. Based on case studies in Bojonegoro Regency, this research study used a qualitative iresearch imethod. The data analysis method iused is an interactive analysis method. So ithe iresearcher iis iinterested iin iconducting iresearch ion